2018
DOI: 10.1042/bcj20180555
|View full text |Cite
|
Sign up to set email alerts
|

Differential receptor selectivity of the FGF15/FGF19 orthologues determines distinct metabolic activities in db/db mice

Abstract: Fibroblast growth factors (FGF) 19, 21 and 23 are characterized by being endocrinely secreted and require co-receptor α-klotho or β-klotho (BKL) for binding and activation of the FGF receptors (FGFR). FGF15 is the rodent orthologue of human FGF19, but the two proteins share only 52% amino acid identity. Despite the physiological role of FGF21 and FGF19 being quite different, both lower blood glucose (BG) when administered to diabetic mice. The present study was designed to clarify why two human proteins with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Evidence from previous studies has shown that FGF19 participates in the synthesis of BA, the balance of glucose metabolism, and the reduction of weight in mice [20][21][22][23]. In accordance with our data, J.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from previous studies has shown that FGF19 participates in the synthesis of BA, the balance of glucose metabolism, and the reduction of weight in mice [20][21][22][23]. In accordance with our data, J.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from previous studies has shown that FGF19 participates in the synthesis of BA, the balance of glucose metabolism, and the reduction of weight in mice [18][19][20][21]. In accordance with our data, J.…”
Section: Discussionsupporting
confidence: 93%
“…Another central question is whether the hepatic improvements by FGF21 are related directly or indirectly. The literature is controversial as direct signaling in hepatocytes in vitro ( 72 ) and liver in vivo ( 73 ) are observed, while the liver-specific KLB KO display unaltered FGF21 sensitivity ( 74 ). The direct effect on liver may depend on the pharmacological dose ( 72 , 75 ), as FGF21 binds with higher affinity toward the FGFR1c/KLB complex compared to the FGFR3c/KLB complex ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is controversial as direct signaling in hepatocytes in vitro ( 72 ) and liver in vivo ( 73 ) are observed, while the liver-specific KLB KO display unaltered FGF21 sensitivity ( 74 ). The direct effect on liver may depend on the pharmacological dose ( 72 , 75 ), as FGF21 binds with higher affinity toward the FGFR1c/KLB complex compared to the FGFR3c/KLB complex ( 76 ). FGFR1c is not expressed by the liver, but FGF21 may mediate its hepatic effect through FGFR3c/KLB signaling ( 76 , 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%